2016
DOI: 10.5539/elt.v9n8p140
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of the Effectiveness of Two Strategies of Etymological Elaboration and Pictorial Elucidation on Idiom Learning: A Case of Young EFL Iranian Learners

Abstract: This study examined the effect of etymological elaboration, pictorial elucidation, and integration of these 2 strategies on idiom learning by L2 learners. A total number of 80 homogeneous intermediate learners studying English at 3 language institutes in Isfahan, Iran, were selected. The intermediate participants were selected as the result of administering an Oxford Placement Test (OPT) to them. Then, the participants were divided into 4 groups of equal size, that is, control, etymological, pictorial, and ety… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
2
1
0
Order By: Relevance
“…The results of the essay analysis have revealed that the essays written by the intermediate group are marked by the presence of metonymy (the total number per group is 13), rather than metaphor (the total number is 8 per group). The predominance of metonymy over metaphor in the intermediate group's essay writing is in concert with previous research findings (MacArthur, 2010;Haghshenas & Hashemian, 2016), which indicate that the usage of metonymy rather than metaphor is associated with the intermediate level of EFL proficiency.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The results of the essay analysis have revealed that the essays written by the intermediate group are marked by the presence of metonymy (the total number per group is 13), rather than metaphor (the total number is 8 per group). The predominance of metonymy over metaphor in the intermediate group's essay writing is in concert with previous research findings (MacArthur, 2010;Haghshenas & Hashemian, 2016), which indicate that the usage of metonymy rather than metaphor is associated with the intermediate level of EFL proficiency.…”
Section: Discussionsupporting
confidence: 87%
“…Then, the corpus was analysed manually for the presence of metonymy and metaphor. Qualitative findings seem to support previous research (MacArthur, 2010;Haghshenas & Hashemian, 2016), which suggests that the use of metonymy tends to be associated with the intermediate level of EFL writing, whilst both metonymy and metaphor are predominantly found in the writing by advanced EFL learners.…”
supporting
confidence: 86%
“…It is regarded useful for two major reasons. First, mastery of literal sense of an idiom leads to a mental image, and understanding the literal origins of the idioms take place at a deeper level of processing than memorization which boosts memory storage (Haghshenas & Hashemian, 2016).…”
Section: Idiomsmentioning
confidence: 99%